2017
DOI: 10.1073/pnas.1703498114
|View full text |Cite
|
Sign up to set email alerts
|

Maize defective kernel mutant generated by insertion of a Ds element in a gene encoding a highly conserved TTI2 cochaperone

Abstract: We have used the newly engineered transposable element to tag a gene that gives rise to a defective kernel () phenotype. requires the autonomous element for transposition. Upon excision, it leaves a short DNA footprint that can create in-frame and frameshift insertions in coding sequences. Therefore, we could create alleles of the tagged gene that confirmed causation of the phenotype by the insertion. The mutation, designated , is embryonic lethal, has a defective basal endosperm transfer (BETL) layer, and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 41 publications
0
18
1
Order By: Relevance
“…The defective kernel (dek) mutants are affected in the development of both the embryo and the endosperm, and were initially generated through ethyl methanesulfonate (EMS) mutagenesis of the pollen (Neuffer and Sheridan, 1980). Only a fraction of the dek mutants have been cloned and functionally characterized (Lid et al, 2002;Qi et al, 2016bQi et al, , 2017aQi et al, , 2017bGarcia et al, 2017;Wang et al, 2017;Dai et al, 2018;Li et al, 2018b). In this study, we analyzed the classic maize mutation dek15, which leads to a reduced endosperm and is embryo lethal.…”
Section: Introductionmentioning
confidence: 99%
“…The defective kernel (dek) mutants are affected in the development of both the embryo and the endosperm, and were initially generated through ethyl methanesulfonate (EMS) mutagenesis of the pollen (Neuffer and Sheridan, 1980). Only a fraction of the dek mutants have been cloned and functionally characterized (Lid et al, 2002;Qi et al, 2016bQi et al, , 2017aQi et al, , 2017bGarcia et al, 2017;Wang et al, 2017;Dai et al, 2018;Li et al, 2018b). In this study, we analyzed the classic maize mutation dek15, which leads to a reduced endosperm and is embryo lethal.…”
Section: Introductionmentioning
confidence: 99%
“…The cloned dek genes in maize are involved in the grain growth and development, especially the synthesis and storage of starches and/or proteins in the endosperm [4][5][6][7]. Our biochemical analysis also showed that the mature grain starch contents of BL33 were significantly lower than those of BL31…”
Section: Predication Of Candidate Genes For the Dek Qtlmentioning
confidence: 66%
“…Totally 783 simple sequence repeat (SSR) markers were chosen from the above chromosomes and 15 of these were integrated into two linkage groups using the genetic population. Of them, the genes of dek1, dek35, dek38 and dek39 have been isolated, and all involved in the synthesis and accumulation of starches and/or proteins in the endosperm [4][5][6][7]. Many Dek mutants have been generated in wheat, but their genetic information remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The Dsg insertion (dsgR102G05) in W22 Zx5 (Zm00001d014121, B73 RefGen_V4) was verified by designing PCR primer pairs, with one gene-specific pair (Supplementary Table 12) from W22 Zx5 and one primer from the Dsg GFP insertion (GFP_AC-DS: TTCGCTCATGTGTTGAGCAT) 92 .…”
Section: Methodsmentioning
confidence: 99%